Organocatalytic Desymmetrisation of Fittig’s Lactones: Deuterium as a Reporter Tag for Hidden Racemisation - Spránitz, Péter; Sőregi, Petra; Botlik, Bence Béla; Berta, Máté; Soós, Tibor (Synthesis, 2019)
Highly enantioselective desymmetrisation of Fittig’s lactones with alcohols is promoted by bifunctional cinchona squaramides. The reactions were carried out with monodeuterated methanol to detect possible hidden racemisation of the stereogenic centre. Current evidence suggests that racemisation was not a relevant process for most substrates; partial erosion of enantioselectivity was only detected with ortho-substituted aryl derivates. The resultant glutaric acid derivatives possess a scaffold that is common in natural products and the compounds are also useful chiral building blocks for further synthetic endeavours.
Keywords: Fittig’s lactone; desymmetrization; bislactone acylal; bifunctional organocatalysis; racemization